The The Roma Perspective and the Roma Question in the Media Mirror : Identity, Self-awareness and Self-view in an Environment of Racialization (Seminar_BG, 2025)
The representation of the Roma point of view and the Roma issue in the Bulgarian digital, media, public, cultural and political space is a topic that remains in the shadows even in the most recent history of Bulgaria. This publication will examine how the Roma point of view on the Roma issue falls into the relevant information spaces and whether the Roma point of view is taken into account in other socially significant topics that directly and indirectly affect the Roma as citizens of the country. I will also try to define the terms "Roma perspective" and "Roma issue". In parallel, I will try to examine to what extent the respective "Roma perspectives" on "Roma" and "non-Roma" topics influence the shaping of the narrative of the "Roma issue" and the "Roma perspective". The publication will try to examine how positive or negative stereotypes and expectations about these phenomena are built – both among the larger society and among the Roma community itself as internalized norms and practices. There will also be a specific focus on how Roma opinion leaders and authorities on Roma and non-Roma issues are formed and recognized. Whether popularity in specific digital dimensions or knowledge and experience on a specific topic prevails, whether proximity to the community or distance from it plays a role. A parallel will also be drawn how methods for the representation of the Roma point of view and the Roma issue are multiplied in a populist way on other topics and are applied to the whole society to shape attitudes for action or inaction.  ReferencesAdichie, C. N. 2009. The Danger of a Single Story. TED Talks. https://www.ted.com/talks/chimamanda_ngozi_adichie_the_danger_of_a_single_story.Angelova, R., Dimitrova, M., Yordanova, G., Pamporov, A., i dr. 2020. Obrazovatelni postizhenia na romskite obshtnosti v Bulgaria. Trast za sotsialna alternativa i Global Metrics. Ltd. https://socialachievement.org/web/files/richeditor/dokumenti/Education%20and%20Employment%20survey%20report%202020.pdf.‌ [in Bulgarian]Arnstein, R. 1969. “A Ladder of Citizen Participation.” Journal of the American Institute of Planners.Asotsiatsia Integro. 2010. Mladi romi napraviha pregled na romite v balgarskia pechat. https://integrobg.org/campain/?p=281. [in Bulgarian]Axner, M. 2019. Healing from the Effects of Internalized Oppression. Ku.edu. https://ctb.ku.edu/en/table-of-contents/culture/cultural-competence/healing-from-interalized-oppression/main.Balgarski Helzinkski komitet. 2002. Etnicheskite maltsinstva v pechata. BHK. Sofia. [in Bulgarian]Bandura, A. 2023. Social Cognitive Theory. John Wiley & Sons, Inc. https://doi.org/10.1002/9781394259069.Barth, F. 1969. Ethnic groups and boundaries. Long Grove: Waweland Press.Bauman, Z., & May, T. 2019. Thinking sociologically (3rd ed.). John Wiley & Sons.Bude, Y. 2021. Godini nared lazhlivi tvardenia za romskata DNK?  DW. 2021. https://www.dw.com/bg/%D1%83%D1%87%D0%B5%D0%BD%D0%B8-%D0%B3%D0%BE%D0%B4%D0%B8%D0%BD%D0%B8-%D0%BD%D0%B0%D1%80%D0%B5%D0%B4-%D0%B4%D0%B0%D0%BD%D0%BD%D0%B8-%D0%B7%D0%B0-%D1%80%D0%BE%D0%BC%D1%81%D0%BA%D0%B0%D1%82%D0%B0-%D0%B4%D0%BD%D0%BA-%D1%81%D0%B0-%D0%B1%D0%B8%D0%BB%D0%B8-%D0%BC%D0%B0%D0%BD%D0%B8%D0%BF%D1%83%D0%BB%D0%B8%D1%80%D0%B0%D0%BD%D0%B8/a-60079423. [in Bulgarian]Burdiyo, P., Vakan, L. 2014. Sotsialni klasi i simvolna vlast. Ciela. Sofia. [in Bulgarian]Byuksenshyutts, U., 2019. „Maltsinstvenata politika v Bulgaria: politikata na BKP kam evrei, romi, pomatsi i turtsi 1944-1989“, Liberalen Pregled. https://www.librev.com/index.php/discussion/bulgaria/3590-maltzinstvenata-politika-v-balgariya-politikata-na-bkp-kam-evrei-romi-pomatzi-i-turtzi-1 [in Bulgarian]Cortés, I. 2021. “Hate Speech, Symbolic Violence, and Racial Discrimination. Antigypsyism: What Responses for the next Decade?” Social Sciences 10 (10): 360. https://doi.org/10.3390/socsci10100360.Dalal, F. 2002. Race, Colour and the Process of Racialization: New Perspectives from Group Analysis, Psychoanalysis and Sociology. New York, NY: Brunner-Routledge.Durkheim, É. 2002. Za razdelenieto na obshtestvenia trud [The Division of Labor in Society, Bulgarian translation]. Translated by Т.Mineva. Sofia, SONM.Eurobarometer. 2023. Discrimination in the European Union. ‌European Commission. https://europa.eu/eurobarometer/surveys/detail/2972.European Commission. 2020. The New EU Roma Strategic Framework for Equality, Inclusion and Participation. https://commission.europa.eu/publications/new-eu-roma-strategic-framework-equality-inclusion-and-participation-full-package_en.  ‌Fairclough, N. 1995. Critical Discourse Analysis: The Critical Study of Language. London: Routledge.Fondatsia S.E.G.A. 2022. Grizha za istinata – sreshtu falshivite novini i antiromskata dezinformatsia. Fondatsia S.E.G.A – Start za efektivni grazhdanski alternativi. 2022. https://cega.bg/wp-content/uploads/2022/07/BG_CARE-4-TRUTH_book_web.pdf [in Bulgarian]Georgiev, V. 2009. Rumyan Rusinov: romskiyat vapros e chast ot balgarskia. https://www.bulgaria-news.bg/category/exclusive/interview/article/post2145.html. [in Bulgarian]Gordon, P. 1964. Assimilation in American Life. New York: Oxford University Press.Grekova, M. 2019.  Kakvo e sbarkano s politikite za " Integratsia na romite v Bulgaria"?  Universitetsko izdatelstvo „Sv. Kliment Ohridski". [in Bulgarian]Habermas, J. 1984. The Theory of Communicative Action, Volume 1: Reason and the Rationalization of Society. Translated by Thomas McCarthy. Boston: Beacon Press.Habermas, J. 1990. Moral Consciousness and Communicative Action. Translated by Christian Lenhardt and Shierry Weber Nicholsen. Cambridge, MA: MIT Press.Habermas, J. 1996. Between Facts and Norms: Contributions to a Discourse Theory of Law and Democracy, trans. William Rehg. Cambridge, MA: MIT Press.Hardiman, R. 1982. White identity development: A process oriented model for describing the racial consciousness of White Americans (Doctoral dissertation). Dissertation Abstracts International, 43, 104A. (University Microfilms No. 82–10330).Hartley, J. 1982. Understanding News. London, New York: Routledge.Hristova, S. 2007. „Obrazat na romite v elektronnite predavania za romite“, In: Integratsia na romite v balgarskoto obshtestvo. Institut po sotsiologia pri BAN. Dostapen ot  https://www.researchgate.net/publication/306031001_Obrazt_na_romite_v_elektronnite_predavania_za_romite#fullTextFileContent.‌ (last seen 11.07.2025) [in Bulgarian]Indzhov, I. 2015. „Obrazat na romite v balgarskia pechat“. Newmedia21.Eu. https://www.newmedia21.eu/izsledvaniq/obrazat-na-romite-v-balgarskiya-pechat-2012/. [in Bulgarian]Indzhov, I. 2023. LGBTI - novata mediyna mishena vmesto romite? Obrazat na maltsinstvenite i uyazvimite grupi v balgarskite medii. (izsledovatelski doklad) Organizatsia „Drom“, https://www.bghelsinki.org/web/files/reports/173/files/2023-indjov--the-image-of-minority-groups-in-the-media.pdf [in Bulgarian]Isaev, O. 2013. “Opitat na promenenite”. Neshto razlichno za razlichnite. https://ognyanisaev.blogspot.com/2013/07/blog-post_23.html. [in Bulgarian]Isaev, O. 2022. Zhurnalistika (g)ol inkluziv: slovesni uydurmi bez savest za troyka predizborni kebapcheta v plik. Marginalia. https://www.marginalia.bg/zhurnalistika-g-ol-inkluziv-slovesni-ujdurmi-bez-savest-za-trojka-predizborni-kebapcheta-v-plik/ [in Bulgarian]Isaev, O. 2023. Rodi me, mamo s kasmet, pa me hvarli na MON. Marginalia. https://www.marginalia.bg/rodi-me-mamo-s-kasmet-pa-me-hvarli-na-mon/ [in Bulgarian]Johnson, L. B. 1965. "Commencement Address at Howard University: to Fulfill These Rights". Тhe American Presidency Project. https://www.presidency.ucsb.edu/documents/commencement-address-howard-university-fulfill-these-rights. Katz, E., and Paul L. 2006. Personal Influence : The Part Played by People in the Flow of Mass Communication. New Brunswick: Transaction Publishers.Klub „Obektiv“. 2013. Vsichko e ezik. Politicheskoto i mediynoto heytarstvo sashto. Balgarski helzinkski komitet. https://www.bghelsinki.org/bg/publication/vsichko-e-ezik-politicheskoto-i-medijnoto-hejtrstvo-ssho. [in Bulgarian]Koen, E. 2016. "Deyan Kolev: Romskata integratsia shte tragne, ako privlechem mnozinstvoto na svoya strana". Marginalia. https://www.marginalia.bg/deyan-kolev-romskata-integratsiya-shte-tragne-ako-privlechem-mnozinstvoto-na-svoya-strana-2/. [in Bulgarian]Kolev, G. 2010. Balgarskata komunisticheska partia i tsiganite prez perioda 1944–1989 g. Tsentar za publichni politiki. Sofia. [in Bulgarian]Lipsitz, G. 1998. The Possessive Investment in Whiteness: How White People Profit from Identity Politics. New York: Temple University Press.‌Marinov, P. 2024. Protivodeystvie na radikalizatsiyata i terorizma v Republika Bulgaria. (Avtoreferat na disertatsia za prisazhdane na ONS „Doktor“ ot Voenna akademia “Georgi Stoykov Rakovski.”) https://rndc.bg/wp-content/uploads/2024/04/auto_pmarinov.pdf. (last seen 11.07.2025) [in Bulgarian]Merton, Robert K. 1948. “The Self-Fulfilling Prophecy”. Antioch Review.Metodieva, Yu. 2017. Lilia Makaveeva: Romite ne tryabva da badat pasivni potrebiteli na darzhavni uslugi. Marginalia. https://www.marginalia.bg/liliya-makaveeva-imame-nuzhda-ot-prozrachnost/. [in Bulgarian]Morgenroth, T., Ryan, M. K., & Peters, K. 2015. The Motivational Theory of Role Modeling: How Role Models Influence Role Aspirants’ Goals. Review of General Psychology, 19(4), 465-483. https://doi.org/10.1037/gpr0000059Nye, Joseph S. 2004. „Soft Power: The Means to Success in World Politics.“ Foreign Affairs. https://doi.org/10.2307/20033985.Pamporov, A. 2009. Sotsialni distantsii i etnicheski stereotipi za maltsinstvata v Bulgaria. Sofia: Institut Otvoreno obshtestvo. https://osis.bg/wp-content/uploads/2018/04/OSI_Publication_Roma_3.pdf [in Bulgarian]Pashov, M. 2022. Istoria na tsiganite v Bulgaria i v Evropa. Roma. Paradigma. https://research-portal.st-andrews.ac.uk/files/278196264/Shakir_Pashov_e_book.pdf [in Bulgarian]Popov, Yu. 2011. „Tsiganite sa badeshteto na Bulgaria“. Dnevnik.bg. https://www.dnevnik.bg/analizi/2011/10/04/1168598_ciganite_sa_budeshteto_na_bulgariia/. [in Bulgarian]Popova, A. 2021. „Romite ne sledva da rabotyat samo po romskite vaprosi“. Bloomberg TV Bulgaria. https://www.bloombergtv.bg/a/16-biznes-start/95659-v-integratsiyata-na-romite-nyama-neuspeshni-politiki-a-neosashtestveni-takiva. [in Bulgarian]Portal Kultura. 2015. “Zashto tezi batkovtsi vikat sreshtu nas?”. Portal za kultura, izkustvo i obshtestvo. https://kultura.bg/web/%D0%B7%D0%B0%D1%89%D0%BE-%D1%82%D0%B5%D0%B7%D0%B8-%D0%B1%D0%B0%D1%82%D0%BA%D0%BE%D0%B2%D1%86%D0%B8-%D0%B2%D0%B8%D0%BA%D0%B0%D1%82-%D1%81%D1%80%D0%B5%D1%89%D1%83-%D0%BD%D0%B0%D1%81/. [in Bulgarian]Schneider, E. and Otterbein, H. 2024. "Kamala Harris Is Making One Big Strategic Break from Hillary Clinton". Politico. https://www.politico.com/news/2024/08/19/kamala-harris-gender-2024-election-00174530Silverman, C. 2007. "Bulgarian Wedding Music between Folk and Chalg: Politics, Markets and Current Directions". Muzikologija. https://doi.org/10.2298/muz0707069s.Spasov, O. 2016. Ezikat na omrazata v Bulgaria. Ezikat na omraza v Bulgaria: riskovi zoni, uyazvimi obekti. Fondatsia „Tsentar za modernizirane na politiki” i Fondatsia „Mediyna demokratsia”. [in Bulgarian]Sue, W., Sue, D., Neville, H., and Smith, L. 2022. Counseling the Culturally Diverse: Theory and Practice. 9th ed. Hoboken, NJ: John Wiley & Sons, Inc.The IHRA. 2020. Working Definitions & Charters. What Is Antigypsyism/Anti-Roma Discrimination?. IHRA. https://holocaustremembrance.com/resources/working-definition-antigypsyism-anti-roma-discrimination.  ‌Tomova, I. 2015. Obrazat na romite v shest elektronni medii. Asotsiatsia Integro. https://integrobg.org/files/Report_hate_speech.pdf (last seen 11.07.2025.) [in Bulgarian]Tomova, I. i dr. 2011. Romite v periodichnia pechat. Asotsiatsia Integro. [in Bulgarian]Van Dijk, T. A. 2000. „New (s) Racism: a Discourse Analytical Approach.“ In : Cottle, S. Ethnic Minorities and the Media. Buckingham, Philadelphia: Open University Press.Vasilev, B. 2016. „Romite – medien obraz i publichni poslania“. Newmedia21.eu. https://www.newmedia21.eu/analizi/romite-medien-obraz-i-publichni-poslaniya/ [in Bulgarian]Vasileva, S. 2004. „Romskata tematika v balgarskoto mediyno prostranstvo -“za” i “protiv” romite, ot i za romite“, v: Bakalova, M. Rolyata na romskite elektronnite medii za integratsiyata na romite. Sofia, , Institut „Otvoreno obshtestvo”. [in Bulgarian]Yordanov, I. 2008. „ Mediyniyat izbor na romite“, V: Romite v Bulgaria–informatsionen spravochnik. Institut „Otvoreno obshtestvo“ – Sofia, 51-53. [in Bulgarian]Zahariev, B. 2024. Rech, sadarzhashta obidi, predrazsadatsi i omraza spryamo romite v sotsialnata media Feysbuk (powerpoint prezentatsia). https://amalipe.bg/wp-content/uploads/2024/01/Presentation.pdf (last seen 11.07.2025.) Fondatsia "Institut Otvoreno obshtestvo - Sofia". [in Bulgarian]
Keywords: Roma; narratives; representation; stereotypes; attitudes; perspectives